Cognitive deficits in the first 24 hours after the onset of first unprovoked generalized Tonic and clonic seizure - Charmchi, Zeinab; Sayadnasiri, Mohammad (International Journal of Epilepsy, 2017)
Background Many people with epilepsy suffer from cognitive deficits as a consequence of their seizure episodes. Relatively few researches have been undertaken to assess the short term impacts of seizure on cognitive function. This study aimed to evaluate changes in cognitive performance in adults with a new onset generalized seizure in the first 24 h after the onset of their attack.Methods After having given informed consent, 40 patients with first episode of unprovoked generalized tonic-clonic seizure were investigated with a neuropsychological test battery (Wechsler Memory Scale III). Their performance was compared with 40 healthy individuals from the patients' companions.Results Newly diagnosed patients had significantly worse performance in paired association recall which is a parameter of verbal memory; other memory parameters showed no significant changes after seizure attack.Conclusion Our data suggested that even with a one-time seizure episode, patients are susceptible to verbal memory impairment.
Keywords: Cognitive performance; Memory; Paired association recall; First unprovoked seizure; Wechsler memory scale III